Improvement of cod and bod removal by advanced oxidation process (AOP) and biological treatment - Norkasmasila Binti Mat Kasa (School of Environmental Engineering University Malaysia Perlis, 2011)
The major problem concerning of environment in water pollution is from industrial wastewater problem which is the dyes pollution. Existing of dyes in the industrial wastewater will make the serious environmental problem due to its high toxicity. Azo dyes are know to have the strong colour , high chemical oxygen demand (COD) and low biodegradability . The treatment of azo dyes industrial effluents in this research are by effect of hydrogen peroxide (H²O²), pH and ozonation time. It is continuing with the single - stage and multi stage of advanved oxidation process (AOP) and biological treatment. The AOP treatment selected is the combination of ozone and hydrogen peroxide (H²O²)